Kompetensi Kepribadian Dominan Dalam Pendidikan Profesi Guru - Fa’iz Nur Abdillah; Nurul Ulfatin; Mustiningsih Mustiningsih (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: Professional teachers are required to have four compulsory competencies, namely pedagogical, professional, personality, and social competencies. Personality competencies are competencies that can not be obtained immediately, but need a coaching process. One of the processes of fostering personality competencies is through teacher professional education programs held at LPTK. The objectives of this study are (1) to explain the dimensions and aspects of personality in professional education of elementary school teachers, (2) to explain strategies for fostering personality competencies in primary school teacher professional education; (3) explains the evaluation of personality competencies in primary school teacher professional education, and (4) explains the impact of personality after being fostered in primary school teacher professional education. The results of the study are: (1) aspects of the dominant personality that are fostered in the professional education of elementary school teachers, namely acting according to norms, confident as a teacher, and responsible; (2) coaching strategies that are used include learning workshop programs, Basic Advance Scouting courses, national defense, Field Experience Practices, and personality curricula, and resource use; (3) evaluations used to measure the personality of participants using evaluations with tests and non-test evaluations; and (4) the impact received after getting personality development is more trusted by the community, and develops oneself in a sustainable manner.Abstrak: Guru profesional diharuskan memiliki empat kompetensi wajib, yaitu kompetensi pedagogis, profesional, kepribadian, dan sosial. Kompetensi kepribadian merupakan kompetensi yang dapat tidak dapat semerta-merta diperoleh, namun perlu proses pembinaan. Salah satu proses pembinaan kompetensi kepribadian adalah melalui program pendidikan profesi guru yang diselenggarakan di LPTK. Tujuan dari penelitian ini adalah (1) menjelaskan dimensi dan aspek kepribadian dalam pendidikan profesi guru sekolah dasar, (2) menjelaskan strategi pemibinaan kompetensi kepribadian dalam pendidikan profesi guru sekolah dasar; (3) menjelaskan evaluasi kompetensi kepribadian dalam pendidikan profesi guru sekolah dasar; (4) menjelaskan dampak kepribadian setelah dibina dalam pendidikan profesi guru sekolah dasar. Hasil penelitian yaitu: (1) aspek kepribadian yang dominan dibina dalam pendidikan profesi guru sekolah dasar, yaitu bertindak sesuai norma, percaya diri sebagai guru, dan bertanggung jawab; (2) strategi pembinaan yang digunakan antara lain dengan program lokakarya pembelajaran, Kursus Mahir Dasar pembina pramuka, bela negara, Praktik Pengalaman Lapangan, dan kurikulum kepribadian, dan pemanfaatan sumber daya; (3) evaluasi yang digunakan untuk mengukur kepribadian peserta menggunakan evaluasi dengan tes dan evaluasi non-tes; (4) dampak yang diterima setelah mendapatkan pembinaan kepribadian adalah lebih dipercaya masyarakat, dan mengembangkan diri secara berkelanjutan.